Circadian secretion rhythm of GLP-1 and its influencing factors - Liu, Chuanfeng; Liu, Yuzhao; Xin, Yu; Wang, Yangang (Frontiers in Endocrinology, 2022)
Circadian rhythm is an inherent endogenous biological rhythm in living organisms. However, with the improvement of modern living standards, many factors such as prolonged artificial lighting, sedentarism, short sleep duration, intestinal flora and high-calorie food intake have disturbed circadian rhythm regulation on various metabolic processes, including GLP-1 secretion, which plays an essential role in the development of various metabolic diseases. Herein, we focused on GLP-1 and its circadian rhythm to explore the factors affecting GLP-1 circadian rhythm and its potential mechanisms and propose some feasible suggestions to improve GLP-1 secretion.